Interactions Between Cells of Sulfobacillus thermosulfidooxidans and Leptospirillum ferriphilum During Pyrite Bioleaching - Li, Qian; Zhu, Jianyu; Li, Shoupeng; Zhang, Ruiyong; Xiao, Tangfu; Sand, Wolfgang (Frontiers in Microbiology, 2020)
Sulfobacillus and Leptospirillum occur frequently in leaching systems. Here we investigated the effects of cells of L. ferriphilum on biofilm formation and leaching performance by S. thermosulfidooxidans. The effects were caused by the presence of L. ferriphilum or an addition of pyrite leach liquor from L. ferriphilum. Data show that the number of attached S. thermosulfidooxidans on pyrite increases, if the pyrite had been pre-colonized by living biofilms of L. ferriphilum, while it decreases if the pre-colonized biofilms had been inactivated. Coaggregation between S. thermosulfidooxidans and L. ferriphilum occurs during the dual-species biofilm formation, but different effects on bioleaching were noted, if the preculture of L. ferriphilum had been different. If L. ferriphilum had been pre-colonized on a pyrite, significantly negative effect was shown. However, if the two species were simultaneously inoculated into a sterile leaching system, the bioleaching efficiency was better than that of a pure culture of S. thermosulfidooxidans. The effect might be related to a metabolic preference of S. thermosulfidooxidans. If S. thermosulfidooxidans performed leaching in a filtered pyrite leachate from L. ferriphilum, the cells preferred to oxidize RISCs instead of ferrous ion and the number of attached cells decreased compared with the control. This study gives an indication that in a short-term multi-species leaching system the role of S. thermosufidooxidans may be related to the time of its introduction.